Exploration of the coping strategies of parents/care-givers in the management of health and rehabilitation problems of their disabled children - Duma, Vivian V. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil(Rehabilitation))--Stellenbosch University, 2012.